Leverage Determinants Analysis Of Manufacturing Companies Registered in Indonesia Stock Exchange 2014-2018 - Mangasi Sinurat; Willy Cahyadi (The Indonesia Capital Market Institute, 2021)
This study aims to determine the effect of liquidity, growth opportunities, profitability and company size on the leverage of manufacturing companies listed on the Indonesia Stock Exchange. The period used in this research is 5 years, starting from 2014 to 2018. The population in this study is 126 manufacturing companies that have been and are still listed on the Indonesia Stock Exchange for the period 2014-2018. The sample selection technique was purposive sampling method and obtained 40 manufacturing companies that were used as samples. The data analysis technique used is multiple linear regression. Based on the results of data analysis, liquidity and profitability partially have a negative and significant effect on Leverage, Growth Opportunity has no effect on Leverage, Firm Size has no effect on Leverage. Based on the Anova test, it is known that the F statistical value is (107.502) with a significance of (0.000). The adjusted R Square value is (0.682 or 68.2%), this is, if the independent variable is statistically significant in influencing the dependent variable, there is an indication of heteroscedasticity. We recommend that if the independent variable is not statistically significant in affecting the dependent variable, there is no indication of heteroscedasticity. This is observed from the significance of the profitability above the 5% confidence level. Keywords: Leverage, Liquidity, Growth Opportunity, Profitability, Company Size